O reconhecimento de si e do outro: uma experiência literária com a leitura subjetiva em sala de aula - Silva, Mariana Carvalho Costa e (2021)
This work is the result of a research performed in the Program for Post-Graduate Professional Master Degree in the Letters Course, in the Federal University of Uberlandia. The motivation for its elaboration came from the necessity of proposing new teaching methodologies turned to literary literacy, and the formation of young readers which may create opportunities for the students, through the subjective dimension in reading, a potential encounter with literature in the classroom. To do so, we traced a course which began with a bibliographic research which passed through official documents, such as BNCC; reflections regarding literary literacy, based on Soares (2001, 2003), Kleiman (1995), Cosson (2012, 2014), Paulino (2004, 2010), Paulino and Cosson (2009); considerations about the subjective dimension of the literary reading according to Barthes (2004), Iser (1996-9), Petit (2008, 2009, 2013), Jouve (2002, 2013); the relevance of the reading journals as expression of subjectivity by the student-reader based in Rouxel (2012a, 2012b, 2014), Souza (2020) and Machado, Lousada and Abreu-Tardelli (2007); the controversy regarding the literary writing in schools from the pondering of Rezende (2018), Andruetto (2012), Antunes (2015), Houdart-Mérot (2013) and Rouxel (2012a); and the conceptions about stories and short stories, under the perspective of literary genres, according to Cortázar (1974), Gotlib (1985), Piglia (2004) and Spalding (2012). However, upon dedicating ourselves to the development of a didactic approach, we were surprised by the pandemic caused by Sars-CoV-2, which suspended the present activities in the Brazilian schools. Given this event, the methodological intervention planned to happen in person with classes from the 8th grade from the Elementary II from a public school in the municipality of Uberlandia – MG, was reconfigured to be applied remotely. We included new perspectives brought by the virtual environment, such as the work with fanfics, considering the statements by Vargas (2015) and Chartier (1999), with the purpose of prioritizing the juvenile protagonism offered by the digital culture. Thus, we arrived to the intervention presented and described in this work, based by the action-research methodology by Thiollent (1986) and supported in Cosson (2012), Andruetto (2012), Bajour (2012), Rouxel (2012b, 2013c) and Pennac (1993). We chose workshops, which objects for aesthetic fruition were fictional stories and short stories which contemplated the reading of literary texts, the listening, speaking and writing – of reading journals, short stories and fanfics. We concluded, thus, that this research may contribute to a change in the scenario of literature classes in which the expression of subjectivity from the students-readers may be the focus and that, thus, through the reading experiences offered by dialogue with the read texts, they may, in an exercise about otherness, identification, and empathy, to better recognize and comprehend themselves, other people and the world around them.